215k views
2 votes
5x - y = -7
4x + 2y = – 14

2 Answers

6 votes

Answer:


\boxed{\sf \ \ x=-2, \ y=-3 \ \ }

Explanation:

Hello,

I assume that you want to solve this system of two equations

(1) 5x - y = -7

(2) 4x + 2y = -14

We will multiply (1) by 2 and add to (2) so that we can eliminate the terms in y

2*(1)+(2) gives

10x - 2y + 4x + 2y = -7*2 -14 = -14 - 14 = -28

<=>

14x = - 28 we can divide by 14 both parts

x = -28/14 = -2

and then we replace x in (1)

5*(-2)-y=-7

-10-y=-7 add 7

-10-y+7=0

-3-y=0 add y

-3 = y

which is equivalent to y = -3

do not hesitate if you have any question

User Fahri
by
5.4k points
2 votes

Answer:

x = -2, y = -3

Explanation:

5x - y = -7

4x + 2y = – 14

Multiply the first equation by 2

2(5x - y) = 2*-7

10x -2y = -14

Add this to the second equation to eliminate y

10x -2y = -14

4x + 2y = – 14

---------------------------

14x = -28

Divide by 14

14x/14 = -28/14

x = -2

Now find y

4x+2y = -14

4*-2 +2y = -14

-8+2y = -14

Add 8 to each side

2y = -6

Divide by 2

2y/2 = -6/2

y = -3

User Bruno Domingues
by
4.8k points